Is Childhood Obesity Associated with Bone Density and Strength in Adulthood?. (23rd May 2010) - Uusi-Rasi, Kirsti; Kannus, Pekka; Pasanen, Matti; Sievänen, Harri
Abstract : Associations between childhood obesity and adult bone traits were assessed among 62 obese premenopausal women, of which 12 had been obese since childhood (ObC), and 50 had gained excess weight in adulthood (ObA). Body composition and bone mineral content (BMC) of the total body, spine, and proximal femur were assessed with DXA. Total cross-sectional area and cortical (diaphyseal CoD) and trabecular (epiphyseal TrD) bone density of the radius and tibia were measured with pQCT. Compared to ObA-group, ObC-group was 5.2 cm taller having 2.5 and 3.5 kg more lean and fat mass, respectively. Depending on the statistical adjustment, ObC-group had 5–10% greater TrD both in tibia and in radius. The remaining bone traits did not significantly differ between the groups. Current preliminary observations bring up an interesting question whether childhood obesity can result in denser trabecular bone in adulthood. However, prudence must be exercised in the statistical adjustment.